RNA Binding Motif Protein 48 Is Required for U12 Splicing and Maize Endosperm Differentiation. Issue 3 (13th February 2019) - Bai, Fang; Corll, Jacob; Shodja, Donya N.; Davenport, Ruth; Feng, Guanqiao; Mudunkothge, Janaki; Brigolin, Christian J.; Martin, Federico; Spielbauer, Gertraud; Tseung, Chi-Wah; Siebert, Amy E.; Barbazuk, W. Brad; et al.
Abstract : A maize RNA splicing factor promotes normal cell differentiation and stops excessive cell proliferation in the kernel via the removal of minor introns during gene expression. Abstract: The last eukaryotic common ancestor had two classes of introns that are still found in most eukaryotic lineages. Common U2-type and rare U12-type introns are spliced by the major and minor spliceosomes, respectively. Relatively few splicing factors have been shown to be specific to the minor spliceosome. We found that the maize ( Zea mays ) RNA binding motif protein 48 (RBM48) is a U12 splicing factor that functions to promote cell differentiation and repress cell proliferation. RBM48 is coselected with the U12 splicing factor, zinc finger CCCH-type, RNA binding motif, and Ser/Arg rich 2/Rough endosperm 3 (RGH3). Protein-protein interactions between RBM48, RGH3, and U2 Auxiliary Factor (U2AF) subunits suggest major and minor spliceosome factors required for intron recognition form complexes with RBM48. Human RBM48 interacts with armadillo repeat containing 7 (ARMC7). Maize RBM48 and ARMC7 have a conserved protein-protein interaction. These data predict that RBM48 is likely to function in U12 splicing throughout eukaryotes and that U12 splicing promotes endosperm cell differentiation in maize.